Alimentação de porcas lactantes com dietas contendo silagem de grãos úmidos de milho e ácidos orgânicos - Weschenfelder, Volnei Antônio (2008)
The objective of this dissertation was to evaluate the performance of lactating sows and their piglets fed with high moisture corn diets with or without acidifiers. Fifteen sows of commercial genetic lines were used in a randomized complete block with three treatments (negative control diet elaborated each 24h; control diet with 0.5% of benzoic acid elaborated each 24h; control diet with 0.5% of fumaric acid elaborated each 24h) with five replications each. Diets elaborated with high moisture corn with benzoic or fumaric acids did not modify (P>0.05) the backfat thickness. The average daily feed intake (7.93kg/NM) of lactating sows was not influenced (P>0.05) by treatments. The average daily weight gain (0.22kg) and average weaning live weight (6.2kg) of piglets were not influenced (P>0.05) by diets with benzoic or fumaric acids. The addition of fumaric acid in diets of lactation sows decreased (P<0.05) the liquid feces frequency in piglets comparated with negative control diet. The addition of acidifiers in diets containing high moisture corn does not alter performance of lactating sows neither their piglets.